2012
DOI: 10.1371/journal.pone.0031616
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Apolipoprotein F Deficiency on High Density Lipoprotein Cholesterol Metabolism in Mice

Abstract: Apolipoprotein F (apoF) is 29 kilodalton secreted sialoglycoprotein that resides on the HDL and LDL fractions of human plasma. Human ApoF is also known as Lipid Transfer Inhibitor protein (LTIP) based on its ability to inhibit cholesteryl ester transfer protein (CETP)-mediated transfer events between lipoproteins. In contrast to other apolipoproteins, ApoF is predicted to lack strong amphipathic alpha helices and its true physiological function remains unknown. We previously showed that overexpression of Apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
(54 reference statements)
2
29
0
Order By: Relevance
“…We previously generated mice with a targeted deletion of the ApoF gene 5 in which the ApoF coding sequence was replaced with a Beta galactosidase reporter cassette. Surprisingly, deletion of the ApoF gene had no discernible effect on circulating lipids or lipoproteins 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously generated mice with a targeted deletion of the ApoF gene 5 in which the ApoF coding sequence was replaced with a Beta galactosidase reporter cassette. Surprisingly, deletion of the ApoF gene had no discernible effect on circulating lipids or lipoproteins 5 .…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that Apo F overexpression reduces HDL cholesterol levels in mice, and results in HDL particles that are more efficient acceptors of macrophage cholesterol 4 . Surprisingly, ApoF deficiency does not substantially alter plasma lipid or lipoprotein levels in mice 5 . In the current study, we considered the possibility that Apo F may reside on lipoproteins for a function other than simple lipid transport and may play an important role in atherosclerosis.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…While treatment with estrogen (30) or estrogen-agonists (31) reduces atherosclerosis without affecting plasma lipids, the underlying mechanism(s) is not completely understood. Gender specific differences in hepatic cholesterol content have recently been reported (32). Several studies have demonstrated an increase in CE hydrolase activity by estradiol (33-35).…”
Section: Discussionmentioning
confidence: 99%
“…ApoF is a lipid transfer inhibitor protein known to inhibit cholesteryl ester transfer protein [31]. Although an overexpression of apoF has been shown to reduce HDL-C concentrations in mice [32], knocking out the apoF gene in mice had no effect on HDL-C concentrations, size and protein content [33]. In humans, apoF has also been positively associated with HDL-C concentrations in normolipidemic men [34].…”
Section: Discussionmentioning
confidence: 99%